The Quality of Priest Services Manifested Through the Activity of Congregation Members in Evangelization - Miga, Yakobus Gaso; Hendriks, Alvyn C. (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study investigates the theological, pastoral, leadership and relational aspects of the pastor's ministry, which are reflected in the activeness of congregation members in the church's mission of evangelization. The descriptive literature study method was used to assess these aspects. The research results show that pastors must have a strong theological understanding, social sensitivity, the ability to build strong relationships with the congregation, and the ability to be a transformational leader. This study shows that the motivations of faith, love, and obedience to God's commands influence the activeness of congregation members in evangelistic missions. Through direct involvement in mission activities, pastors function as agents of transformation and serve as role models in building an evangelical culture in the church. This study increases our understanding of the complex relationship between the quality of pastors' ministry and congregation members' participation in church evangelism. Some practical consequences of these findings include establishing new methods to enhance the pastor's role in guiding and motivating congregations and creating an environment that supports participation in the church's evangelistic mission.